Sex Differences in Attention-Deficit/Hyperactivity Disorder (ADHD): Short Literature Review - Ositkovska, Oleksandra; Bayer, Oхana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The review of the latest foreign literature on the issue of sex differences in ADHD carriers is presented. The analysis of theories on the causes of the prevalence of the disorder among boys and girls is presented, and minor sex differences are highlighted. Therefore, ADHD is more common among boys than among girls, which leads to arguments about the difference valid in the prevalence of the disorder among men and women. Also, many researchers have noticed certain differences in the symptoms and behaviour of girls compared to boys, both in childhood and adulthood.Boys and girls with ADHD appear to be more similar than different, and usually the symptoms are not sex specific, but still there is a difference. In general, these differences are manifested in the fact that girls have problems with the emotional sphere and the predominant inattentive symptoms of ADHD, while boys have problems with the behavioural sphere and the predominant impulsive and hyperactive type of ADHD. Moreover, boys are more aggressive in behaviour than girls, although girls are more likely to manifest verbal aggression than their female peers, who do not have the disorder.It has been found that the difference in the prevalence of the disorder among males and females can be described by the Cognitive Endophenotype Theory, which assumes the influence of generally accepted endophenotypes on the severity of ADHD, that means processing speed, inhibition and working memory. This theory does not preclude theories such as the Mean Difference Model and the Variance Difference Model, which state that men on the average have more severe symptoms than women, and thus the scale of the severity of the ADHD among boys is much wider than among women.
Keywords: cognitive differences; behavioural disorder; psychosocial differences; ADHD symptoms; sexual characteristics